New Kinds of Smart : Teaching Young People to Be Intelligent for Today's World. - Lucas, Bill (McGraw-Hill International (UK) Ltd., 2010)
New Kinds of Smart presents the most important of these changes to practising teachers and educators, and invites them to think about their implications for school.